2014
DOI: 10.1007/s11356-014-3447-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of carbon nanospheres using fallen willow leaves and adsorption of Rhodamine B and heavy metals by them

Abstract: This paper focuses on the synthesis of carbon nanospheres (CNSs) using fallen willow leaves as a low-cost precursor. The scanning electron microscopy (SEM) image and transmission electron microscopy (TEM) image demonstrated that the structure of synthesized CNSs was spherical, with a diameter of 100 nm. The crystal structure and chemical information were characterized by Raman spectrum and energy-dispersive spectrum (EDS), respectively. BET results showed that the CNSs had a larger specific surface area of 294… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…From the expression of Eq 8, the dimensionless equilibrium separation factor indicated that a pattern of 0< R L < 1 was followed, which indicated favourable adsorption of RhB on acid modified banana peel. The adsorption capacity ( q m ) of the adsorbent (9.5220 mg / g ) was observed to be higher than the adsorption of RhB onto banana pith (8.5 mg / g ) [43], carbon nanosphere (1.15 mg / g ) [44], and Tamarind fruit shell carbon (3.94 mg / g ). On the other hand, the Freundlich isotherm fitted better for the reduction of COD, with an R 2 value of 0.9642 compared to the Langmuir isotherm (0.9548).…”
Section: Resultsmentioning
confidence: 99%
“…From the expression of Eq 8, the dimensionless equilibrium separation factor indicated that a pattern of 0< R L < 1 was followed, which indicated favourable adsorption of RhB on acid modified banana peel. The adsorption capacity ( q m ) of the adsorbent (9.5220 mg / g ) was observed to be higher than the adsorption of RhB onto banana pith (8.5 mg / g ) [43], carbon nanosphere (1.15 mg / g ) [44], and Tamarind fruit shell carbon (3.94 mg / g ). On the other hand, the Freundlich isotherm fitted better for the reduction of COD, with an R 2 value of 0.9642 compared to the Langmuir isotherm (0.9548).…”
Section: Resultsmentioning
confidence: 99%
“…RhB dye is carcinogenic, neurotoxic and causes , eyes, respiratory tract and gastrointestinal tract irritation, with developmental and reproductive toxicity in both humans and animals . It also causes burning sensation, laryngitis, coughing, shortness of breath, wheezing, vomiting, nausea, chest pain, headache, subcutaneous tissue borne sarcoma equivocal tumor [17][18][19][20]. It increases hypothalamic cell apoptosis and have been reported to cause disruption of hormonal balance [21].…”
Section: Table 1 Molecular Structure and Some Physicochemical Propermentioning
confidence: 99%
“…1, are the most commonly employed adsorbents for metal ion removal from wastewater owing to their large specific surface area and concentrated pore distribution [36,37]. Moreover, they exhibit a great mechanical property and excellent structural stability under extreme conditions (e.g., high temperature and strong acidic/alkaline conditions) [38][39][40].…”
Section: Introductionmentioning
confidence: 99%